Higgsov mehanizem - Fridman, Mitja (Matrika, 2016)
In this article the Higgs mechanism is presented, which describes generation of mass of elementary particles. The Lagrange formalism, with which the continuous scalar and vector fields are considered, is introduced. Then the spontaneos symetry breaking, which is also present within the Higgs mechanism, is shown on an example of a ferromagnet. The theoretical model of the Higgs mechanism is described later. At the end, the masses of the weak gauge bosons and the Higgs boson in the standard model (SM) are mentioned.
Keywords: elementary particle physics; fizika osnovnih delcev; Higgs mechanism; Higgsov mehanizem; Standard model; Standardni model